Dual inverter with a floating bridge controlled by a vectorial voltage modulator - Fernao Pires, Vitor (2019)
This paper presents a new control strategy based on a voltage modulator for a dual inverter with a floating bridge. This converter is characterized by a multilevel operation with two conventional two-level voltage source inverters and a single DC voltage source. The proposed control and modulation scheme allows a fast and robust operation of the inverter. The voltage modulator will allow the regulation and stability of the voltage capacitor of the floating bridge. It was also developed to provide an asymmetrical operation of the DC voltages (single DC source and capacitor). Due to this, high output voltage levels will be ensured. Several simulation results will be provided to show the characteristics of the proposed system.